Liberałowie w Parlamencie Europejskim - KRUK, ALEKSANDRA (Rocznik Integracji Europejskiej, 2012)
The Liberals have forced their own beliefs through since European structures began to emerge, but their impact on the concept of integration was weaker than that voiced by the Christian Democrats and the Social Democrats. Factional activity in the European Parliament is another form of the operation of political parties, alongside traditional international party congresses. The paper presents the projects and views of liberal politicians on the process of European integration. Particular attention is paid to the opinions of Gaetano Martino, Cornelis Berkhouwer, Simone Veil, Pat Cox, Graham Watson and Andrew Duff.